Treatment of latent tuberculosis in a child with mucopolysaccharidosis type I receiving enzyme replacement therapy: A case report - Vasilevska, Lauma; Auzenbaha, Madara; Grinfelde, Ieva; Skangale, Anita (Frontiers in Pediatrics, 2022)
Mucopolysaccharidosis type I S (MPS IS) is a rare autosomal recessive lysosomal storage disorder caused by mutations in the IDUA gene, leading to a deficiency of the enzyme alpha-L-iduronidase. Enzyme replacement therapy (ERT) reduces lysosomal storage in the liver and improves clinical manifestations. To date, there are no published reports of tuberculosis (TB) treatment in MPS IS patients receiving ERT and as such it is not known whether both conditions can be treated simultaneously. Here, we report the case of a 14-year-old male with MPS IS receiving ERT with laronidase who was diagnosed with a latent TB infection after being in contact with a multi-drug-resistant TB patient. He received prophylactic TB treatment with moxifloxacin for six months. No complications were reported and there has been no active TB disease. Our case report demonstrates that TB and MPS IS can be treated simultaneously without serious adverse effects.